Computational studies of glycolipids and their interactions with carbon nanotubes / Zahrabatoul Mosapour Kotena - Mosapour Kotena, Zahrabatoul (2015)

(untitled)
Carbon nanotubes (CNTs) have attracted the attention of many researchers due to their unique mechanical, structural, and electrical properties, and their apparent usefulness in nanotechnology, nanoelectronics, biosensors, biotechnology, biomedicine, and energy storage. Single-walled nanotubes (SWNTs) could be dispersed by surfactants, such as glycopyranoside, which is a family of non-ionic surfactants, from the more generic class of glycolipids found in nature, especially in biological membranes. Hydrogen bond is a dominant factor in different biological processes. This thesis focuses on the knowledge of the hydrogen bond formation in non-ionic surfactant such as glycolipids. Subsequently, we examined the effect of one of these surfactants on SWNTs via quantum chemical calculations. Density functional theory calculations on two glycosides, namely, n-octyl-β-D-glucopyranoside (C8O-β-Glc) and n-octyl-β-D-galactopyranoside (C8O-β-Gal), were performed for geometry optimization at the B3LYP/6-31G level. Both molecules are stereoisomers i.e. both are epimers. They differ only in the orientation (axial vs equatorial) of the hydroxyl group at the C4 position. Thus, it is interesting to electronically investigate the effect of the direction of the hydroxyl group at the C4 position. The structure parameters of X-H…Y intra-molecular hydrogen bonds were analyzed and the nature of these bonds and the intra-molecular interactions were considered using the atoms in the molecules approach. Natural bond orbital analysis was used to determine the effective non-bonding interactions. These results showed that, while C8O-β-Glc possess only one hydrogen bond, C8O-β-Gal has two intra-molecular hydrogen bonds, which further confirms the anomalous stability of the latter in self-assembly phenomena. iv In addition, density functional theory calculations on α/β-D-mannose (α/β-Man) and the corresponding glycosides of n-octyl-α/β-D-mannopyranoside (C8O-α/β-Man) were carried out for geometrical optimization and stability predictions at the B3LYP/6-31G level of theory. These compounds are anomerically related, since they differ by only the orientation of the hydroxyl group at the C1 position. The aim of this study is to investigate the effect of the hydroxyl group’s orientations at the C1 position on the intra-molecular interactions and the conformational stability of these isomers. The structural parameters of X-H…Y intra-molecular hydrogen bonds were analyzed, while the nature of these bonds was taken into account using the atoms in molecules approach. Natural bond orbital analysis was used to determine the effective non-bonding interactions. The results showed that while α-anomers possesses only one intra-molecular hydrogen bond, β-anomers possesses two intra-molecular hydrogen bonds, which further confirms the anomalous stability of the latter in the self-assembly phenomena. In order to study the interaction between CNTs and surfactants, we report on a density functional theory calculation at the B3LYP/6-31G level of theory performed for the purpose of predicting the reactivity governing the nucleophilic and electrophilic attacks on the external surface of a SWNTs. The computational results predicted that glycolipid could induce in a strong interaction on the surface of the SWNT in both gas and aqueous phases. Therefore, surfactants disperse SWNTs in aqueous solutions, mainly via hydrophobic/hydrophilic interactions, where the hydrophobic tail of the surfactant molecule adsorbs on the surface of SWNT, while the hydrophilic head associates with water for the purpose of dissolution.